TECHNOLOGICAL AND DIGITAL GAP: THE IMPACT OF ACCESS TO TECHNOLOGY, DIGITAL RESOURCES, AND ONLINE LEARNING PLATFORMS ON EDUCATIONAL EQUITY AMONG DIFFERENT ETHNOCULTURAL GROUPS (Konferensiyalar | Conferences, 2024)
This article examines the impact of access to technology, digital resources, and online learning platforms on educational equity among diverse ethnocultural groups. Disparities in technology ownership and internet connectivity disproportionately affect students from economically disadvantaged and minority backgrounds, contributing to inequities in educational opportunities. Through a mixed-methods approach combining quantitative surveys and qualitative insights, this study identifies barriers such as cost, language, and cultural relevance that hinder equitable technology access. Findings emphasize the importance of subsidized technology, culturally relevant resources, educator capacity building in culturally responsive pedagogy, improved internet infrastructure, and community partnerships to bridge the technological gap and promote educational equity.